Energy from Wind : Wind Farming - Kopp, Megan (St. Catharines, Ontario ; Crabtree Publishing, 2016)
"Our planet's weather offers some incredible solutions to our growing energy needs, and one of those solutions is wind power. Offshore and onshore wind farms are an increasingly familiar sight in many countries around the world. Wind farms tap into this clean, sustainable, and renewable form of energy. Find out how wind power works, where in the world it is being used, and how this green energy supply could be one answer to the energy problems that face us today."--
What is energy? -- Wind 101 -- Time for wind power -- All about turbines -- Farming the wind -- Offshore breezes -- Where in the world? -- Powerful tales -- Spotlight on North America -- Clean power positives -- Wind power issues -- Taking the future by storm -- Power up!.
Includes index.
Keywords: Wind power -- Juvenile literature; Power resources -- Juvenile literature; Clean energy industries -- Juvenile literature; Wind power plants -- Juvenile literature